Compressive and shear strengths of the ductile closed-cell Kelvin and Weaire-Phelan foams along the lattice direction [100]. (November 2018) - Chen, Youming; Das, Raj; Battley, Mark; Xu, Zhigang
Abstract: The compressive and shear responses of the closed-cell Kelvin and Weaire-Phelan foams along the lattice direction [100] were studied using explicit dynamic analyses in this work. Expressions describing the relationship of compressive and shear strengths to relative density were developed for these two foams. The compressive and shear strengths of the Kelvin and Weaire-Phelan foams are found to increase quadratically with relative density at low relative densities and linearly at high relative densities. This is because elastic buckling followed by material yielding cause the failure of low relative density foams, while large deformation and material yielding is the main cause of failure for high relative density foams. Cell wall buckling and local material yielding only cause reduction in global stiffness. Ductile foams fail globally when a certain amount of material has yielded, forming a plastic band across the foams. Shear buckling occurs in foams with very low relative density under shear. Highlights: Foam strength increase quadratically with relative density at low relative densities. Foam strengths increase linearly with relative density at high relative densities. The shear strengths of the two foams increase nearly linear with relative density. Cell wall buckling and local material yielding only cause reduction in global stiffness. Ductile foams fail globally when a plastic band across the foams.